Enhancing performance of the health information department of a hospital using lean Six Sigma methodology. (1st January 2013) - Bhat, Shreeranga; Jnanesh, N.A.
The study addresses the issue of longer turn around time (TAT) of health records preparation process in the health information department (HID) of a corporate hospital in India. Because of the longer TAT of the health records preparation process, other activities of the department were held up, creating a work in process inventory of records in the department. This paper explores how a small-capacity corporate hospital can use a systematic methodology to move towards world-class quality level. A rigorous Lean thinking and Six Sigma define-measure-analyse-improve-control (DMAIC) approach was used to analyse the existing process and root causes of longer TAT. Lean operational principles were used to improve and sustain the process. As a result of the project, average TAT was reduced from 52 min to 39 min and standard deviation was reduced to 0.43 min from 2.33 min for a batch of 10 health records.